ARCHITECTURAL DESIGN OF BAKUNJANGAN TOURISM APPLICATION IN BANJARMASIN CITY USING ZACHMAN FRAMEWORK - Muhammad Hidayat; Dina Afriani (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: The implementation of Enterprise Architecture (EA) in Banjarmasin city's tourism sector is essential to improve the effectiveness of information provided to tourists accessing electronic-based services. Unfortunately, there are some crucial challenges to the fundamental requirements of EA in the tourism sector. There is still partial implementation, a lack of understanding of the technological advances used in Banjarmasin city tourism promotion, a lack of understanding of the implementation in an application architecture framework design and the technology to be used, not having good documentation in the design of application systems and slow services in tourism promotion. There is no certainty of normative standardization for system development operating procedures. This research aims to design the Zachman Framework (ZF) Application architecture as an Enterprise Architecture Planning (EAP) methodology, to visualize spatial data. This application is designed to assist users in displaying spatial data in the form of interactive maps that can be accessed via the internet. The software development method used is the iterative and incremental method with the Zachman Framework approach to application design. Data was collected through surveys and interviews at the Department of Culture, Youth, Sports and Tourism (DISBUDPORAPAR) of Banjarmasin City, with the current number of tourism data being 55 tourist attractions. This application can later be used to introduce tourist attractions in Banjarmasin City to the wider community, including tourists visiting this city.            Keywords: enterprise architecture (ea), tourism, zachman framework (zf) Abstrak: Penerapan Enterprise Architecture (EA) disektor pariwisata kota Banjarmasin amatlah penting untuk meningkatkan efektivitas informasi yang diberikan kepada wisatawan yang mengakses layanan berbasis elektronik. Sayangnya, ada beberapa tantangan krusial terhadap persyaratan mendasar EA di sektor pariwisata. Masih ada yang diimplitasikan seara parsial, kurangnya pemahaman dalam kemajuan teknologi yang digunakan pada promosi pariwisata kota Banjarmasin, kurangnya pemahaman akan implimentasi dalam sebuat perancangan kerangka kerja arsitektur aplikasi dan teknologi yang akan digunakan, tidak memiliki dokumentsai yang baik dalam perancangan sistem aplikasi serta pelayanan yang lambat dalam promosi pariwisata. Belum adanya kepastian standarisasi normatif untuk prosedur operasi pengembangan sistem. Penelitian ini bertujuan untuk merancang arsitektur Aplikasi Bakunjangan Zachman Framework (ZF) sebagai metodologi Enterprise Architecture Planning (EAP),  untuk memvisualisasikan data spasial. Aplikasi ini dirancang untuk membantu pengguna dalam menampilkan data spasial dalam bentuk peta interaktif yang dapat diakses melalui internet. Metode pengembangan perangkat lunak yang digunakan adalah metode iteratif dan inkremental dengan pendekatan Zachman Framework untuk perancangan aplikasi. Data dikumpulkan melalui survey dan wawancara pada Dinas Kebudayaan, Kepemudaan, Olahraga dan Pariwisata (DISBUDPORAPAR) Kota Banjarmasin, dengan jumlah data pariwisata saat ini yakni 55 tempat wisata. Aplikasi ini nanti dapat digunakan untuk memperkenalkan objek wisata di Kota Banjarmasin kepada masyarakat luas, termasuk wisatawan yang berkunjung ke kota ini. Kata kunci: enterprise architecture (ea), pariwisata, zachman framework (zf)